THE IMPACT OF DIGITAL TOOLS ON IMPROVING LITERACY: A SYSTEMATIC LITERATURE REVIEW - Loso Judijanto; Suroso Suroso (CV. ADIBA AISHA AMIRA, 2025)
This study aims to evaluate the impact of digital tools on improving literacy through a systematic literature review. The results of the study show that digital tools, such as e- books, educational applications, and online learning platforms, have great potential to improve student literacy by providing flexible access and a variety of relevant reading sources. Digital tools also offer interactive features that can increase student engagement and understanding, as well as provide instant feedback that aids the learning process. However, this study also identifies several challenges, including the digital divide and the potential for disruption that can result from uncontrolled use of digital tools. Optimising the benefits of digital tools for improving literacy requires collaboration from various parties, such as teachers, parents, and education policymakers, as well as adequate training for educators. Overall, when used correctly, digital tools can make a significant contribution to improving student literacy.